EFL Students' Perceptions Towards The Utilization of Wordwall.Net in Learning Grammar - Salsabila, Queen; Budianto, Langgeng (English Edu: Journal of English Teaching and Learning, 2023)
Grammar is often considered difficult to learn. With the development of technology in education, this difficulty can be overcome using media that integrate with technology. One of the media that can be used for learning grammar is Wordwall.net. Many studies have examined the use of Wordwall.net in the learning process, one of those in the process of learning grammar. As a result, this research explores EFL students' perception of using Wordwall.net as media for learning Grammar by looking at their acceptance based on four variables of the Technology Acceptance Model (TAM), which are perceived Ease of Use (PEOU), Perceive Usefulness (PU), Attitude Towards Using (ATU), and Behavioral Intention to Use (BITU) and what difficulties they faced during the implementation of Wordwall.net in learning Grammar which focuses on eleventh-grade students MAN 1 Gresik as the novelty of this research. This research used a mixed method. With a sequential explanatory research design, the instruments used in this study are questionnaires and interview guidelines. The questionnaires use the Likert scale to measure the data. From the analysis process, students perceive that Wordwall.net is easy to use and useful. In addition, students show a positive attitude towards using Wordwall.net in grammar learning, and students intend to use Wordwall.net in the process of learning Grammar in the next meeting. Difficulties faced by students when using Wordwall.net is the less clear instructions, internet problems, and students' device. Thus, students accept the use of Wordwall.net in grammar learning, and the source of problems that arise are external problems. Furthermore, Wordwall.net can be implemented in the learning grammar process because this game brings a positive impact based on students' perceptions. The game is easy to use, simple, fun, and increases their learning motivation.